PEMBELAJARAN FIQIH MATERI ZAKAT BERWAWASAN INTEGRATIF INKLUSIF - Athiroh, Siti; Dwi Herti, Yeti; Aditian, Faiz (Penerbit CV Tentrem Karya Nusa, 2019)
There are so many problems that arise in teaching and learning activities, such as the limited ability of teachers and supporting components of the learning process. One way to solve this problem is to use the right learning approach. This needs to be done to facilitate the occurrence of the teaching and learning process. One of them is by using an integrated integra approach. The current process of learning activities must be able to be integrated between one ascientific discipline and another. Included in this is the learning of jurisprudence material. Jurisprudence, which is part of the Islamic Education family, must be well conveyed. Therefore, an integrative inclusive approach can be a way out to solve problems that arise so that the purpose of learning fiqh material for zakat can be achieved well.Key Words: Zakat Learning, Learning Approach, Integrative Inclusive.